Occupational Stress, Knowledge Sharing, Perceived Organisational Support and General Well Being amongst IT personnel in Malaysia - Thenuwara, Chathuri Upeksha (2011)
The IT industry has grown to prominence over the last decade, with IT personnel from all domains of IT knowledge being increasingly needed to match this growth. The IT profession presents a stressful environment. However, little theoretical and empirical research is carried out on the factors which affect IT personnel. The purpose of this study is to identify whether there exists relationships between Occupational Stress, Knowledge Sharing, Perceived Organisational Support and General Well-being amongst IT personnel in Malaysia. Additionally, the study also intends to identify moderator effects by Perceived Organisational Support on relationships between stressors and Knowledge sharing, and stressors and General Well-being. A web based questionnaire, accessible by a hyperlink distributed to respondents via email invitation only, was used to gather data from the sample demographic. The responses were analysed quantitatively through statistical techniques.In terms of Knowledge Sharing (KS), the findings indicate that Perceived Organisational Support (POS) and Career Concerns (CC) affected KS. The interactions effects indicated that effect of stressors on KS were either buffered or exacerbated by POS. In terms of General Well-being (GWB), the significant predictors were Relationship with Others (RO), System Maintenance (SM), Role Ambiguity (RA), and POS. Although the F test revealed there was an interaction effect, closer analysis of the individual cross products showed no significant values.